The use of Cattapa Leaves Terminalia cattapa as Preventive and Curative Methods in Patin Catfish Pangasionodon hypophthalmus Infected With Aeromonas hydrophila - D. Wahjuningrum; N. Ashry; Sri Nuryati (Jurnal Akuakultur Indonesia)
Motile Aeromonad Septicaemia (MAS) caused by Aeromonas hydrophila induced serious epidemics of ulcerative disease in freshwater fish including patin catfish Pangasionodon hypophthalmus. In vitro study for antibacterial test of cattapa leaves Terminalia cattapa (TC) were done previous to the in vivo test. The in vitro susceptibility test was performed at the dosages of 30, 60 and 90 g/l TC. At the in vivo test, fish were injected intramusculary with TC at the dosages of 60 g/l for the prevention and 120 g/l for curative efficacy. Results from blood picture, clinical sign and mortaliyt showed that TC were better and more effective as preventive than curative for MAS in patin catfish.